2020
DOI: 10.1002/awwa.1594
|View full text |Cite
|
Sign up to set email alerts
|

Aquifer Storage and Recovery: Can an Updated Inventory Predict Future System Success?

Abstract: A 2013 inventory of ASR systems was updated in 2019 to evaluate project parameters and determine which variables are best at predicting the success of future ASR projects.With a time frame of June 2013 through October 2019, the revised inventory and analysis included data on new ASR sites and existing sites whose status had changed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Miszczak et al conduct a general survey of results of pollution sources and analysis of pollution sources in a city and put forward pollution prevention and control measures [7]. Bloetscher et al identified beverage manufacturing, papermaking and paper products, food manufacturing, and agricultural and sideline food processing industries as typical industries to reduce oxygen demand pollution through the summary, analysis, and research on the census data of pollution sources and focused on the generation, emission, and treatment of five-day biochemical oxygen demand in four industries [8]. Liu et al analyzed the production, emission characteristics, and pollution status of pollutants in Jingjiang City, Jiangsu Province, by using the census data of pollution sources and social statistical data and pointed out that while industrial pollution is paid attention to, domestic pollution and agricultural pollution cannot be ignored [9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Miszczak et al conduct a general survey of results of pollution sources and analysis of pollution sources in a city and put forward pollution prevention and control measures [7]. Bloetscher et al identified beverage manufacturing, papermaking and paper products, food manufacturing, and agricultural and sideline food processing industries as typical industries to reduce oxygen demand pollution through the summary, analysis, and research on the census data of pollution sources and focused on the generation, emission, and treatment of five-day biochemical oxygen demand in four industries [8]. Liu et al analyzed the production, emission characteristics, and pollution status of pollutants in Jingjiang City, Jiangsu Province, by using the census data of pollution sources and social statistical data and pointed out that while industrial pollution is paid attention to, domestic pollution and agricultural pollution cannot be ignored [9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, some ASR wells in California, USA, have not been operational for several years due to limited water availability for recharge. 4,61 Periods of inactivity between recharge operations can alter the geochemical response induced by future MAR operations as observed in Hillsboro, Florida, USA, where As concentrations were declining with successive ASR cycles but sharply rebounded after injection resumed following five years of inactivity. 122 The chemical composition of the recharge water is a key factor determining geochemical impacts to the receiving aquifer.…”
Section: Water Quality Considerations For Thementioning
confidence: 99%
“…First, recharge water physically displaces native groundwater (Figure ), while, in most cases, migrating radially away from the injection or infiltration area. Reported injection rates at ASR wells in the United States vary from approximately 757 to 8705 m 3 day –1 with typical injection and withdrawal rates of approximately 3785 m 3 day –1 (1 million gallons per day). , Near the recharge location, the groundwater flow field is controlled by MAR-induced fluxes and is increasingly impacted by the regional-scale flow patterns at farther distances. Idealized conceptual models represent the recharge-impacted zone as a homogeneous “bubble” surrounding the injection well.…”
Section: Overview Of General Mar Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these high conductive zones are very small (less than 8 m) for the medium-to large-scale ASR (injection rate >100 m 3 /day), which may not be suitable for a large-scale injection in the agricultural fields (excess water from low-lying areas in that area). Like in the ASR wells of the United States, where the injection rates were reported from 757 to 8,705 m 3 /day with an approximate recovery rate of 3,785 m 3 /day (Bloetscher, 2015;Bloetscher et al, 2020). The previous ASR guidelines suggest that the large-scale ASR should have high transmissivities with relatively large aquifer thickness (more than 8 m) so that a large amount of water can be injected efficiently and economically (Stuyfzand et al, 2002;Pavelic et al, 2006;Izbicki et al, 2010;Page et al, 2014;Sultana et al, 2015).…”
Section: Nalanda University Campus Wellmentioning
confidence: 99%